CARDIAC SYNCOPE DUE TO ATRIAL FIBRILLATION IN SLOW VENTRICULAR RESPONSE WITH PAUSE AS A CLINICAL MANIFESTATION OF HYPERTHYROIDSIM - Jaji, Elham; Mandangan, Shareefa Huda; Amil, Walid; Chiong, Lowe; Barrera, Jerome; Isnani, Sarah Laida (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Hyperthyroidism commonly affects the heart causing cardiac arrhythmias particularly sinus tachycardia or supraventricular tachyarrhythmias. Atrial fibrillation (AF) in slow ventricular response is typically not reported in such patients. CASE A 58-year-old male without co-morbidities initially consulted at the emergency department due to body malaise. At the ER, he had sudden onset of loss of consciousness. Initial ECG showed atrial flutter with pause. He was subsequently admitted at ICU where further work up was done. CONCLUSION Thyrotoxicosis exerts clear influences on electrical impulse generation and conduction. Numerous possible mechanisms could be considered for the effect of thyroid hormones on AF risk. Reentry has been assumed as one of the main mechanisms leading to AF. However limited literature talks about AF in slow ventricular response with pauses in hyperthyroid patients. In theory, if the patient achieved euthyroid state, ideally symptoms should improve, nonetheless pacemaker was opted for this patient.